Evaluation of antihyperlipidemic activity of ethanolic root extract of Glycyrrhiza glabra Linn. - Tyagi, Priya; Sharma, Satish Kumar; Kumar, Pawan (Journal of Drug Delivery and Therapeutics, 2018)
Glycyrrhiza glabra Linn. is an Indian medicinal plant demonstrated to exert multiple health cures. This plant grows naturally in tropical, subtropical and temperate regions. It is traditionally used as anti-acne, anti-arthritic, anti-convulsant, anti-diabetic, anti-microbial, anti inflammatory, wound healing, anti-oxidant, anti-platelet, anti-stress and nootropic, anti-viral, diuretic and gastroprotective. The antihyperlipidemic effect of ethanolic root extracts of Glycyrrhizaglabrawas studied in wistar rats using High Fat Diet (FD) induced hyperlipidemic model, at the doses of 400 mg/kg body weight. The efficacy of extract was compared with standard drug simvastatin. The ethanolic extracts, significantly decreased the serum lipid profile level in a dose dependent manner in wistar rats. Ethanolic extracts at 400 mg/kg have shown significant antihyperlipidemic action. These results support the fact that this plant is used traditionally as antihyperlipidemic. The study will help in exploring new plant source as an antihyperlipiedemic agent which can minimize the risk and side effects as compared to that of conventional medicine. Keywords: Glycyrrhizaglabra, Antihyperlipidemic Activity, Simvastatin, High Fat Diet (FD) induced hyperlipidemic model.